Innovative E-Module : Addressing the Challenges of IMTAQ Value Needs in the Digital Era at Serirama YLPI High School Pekanbaru - Diva Mulya Sari; Siti robiah (Lombok Institute, 2024)
This study aims to determine the need for an integrated E-Module of IMTAQ values ​​by teachers and students at SMA SERIRAMA YLPI. This E-Module is an electronic-based module presented via a computer or Android device and contains text, images, and videos that include elements of IMTAQ values. This research was conducted at SMA SERIRAMA YLPI Pekanbaru in the 2024/2025 academic year, using a qualitative descriptive research method. From the results of interviews conducted by researchers with biology teachers and 10 grade XI students of SMA SERIRAMA YLPI Pekanbaru, it is known that the teaching materials used by teachers are limited to printed books, and teachers have never integrated IMTAQ values ​​​​in the biology learning process. Data analysis showed that teachers and students at SMA SERIRAMA YLPI PEKANBARU need an E-Module that integrates IMTAQ values ​​​​to shape students' character to be better.